Pengaruh Sukuk To Equity Ratio, Current Ratio, Debt To Equity Ratio dan Size Terhadap Profitabilitas Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2018 - muhammad suhaidi (Jurnal Ilmiah Ekonomi Islam, 2022)
The company's profitability can be interpreted as a prospect or future, many factors can affect the level of profitability of a company, so companies are required to make efforts to obtain maximum profit. One indicator of the company's profitability can be seen from the return on assets of the company itself. The factors in question that can affect the company's profitability include the company's ability to carry out financing, meet its short-term debt, the company's ability in capital structure policies and how the company utilizes all its assets. Based on the above background, this study was conducted to examine and examine the effect of sukuk to equity ratio, current ratio, debt to equity ratio and size on the profitability of companies listed on the Indonesia Stock Exchange in 2013-2018. The source of data in this study comes from secondary data. The data collection technique uses documentation studies in the form of statistics on the development of companies that issue sukuk ijarah and data published by the Indonesia Stock Exchange and the Financial Services Authority. While the data analysis technique in this study used multiple linear regression analysis techniques. The results showed that the simultaneous issuance of Sukuk Ijarah, Current Rastio, Debt To Equity Ratio and size had a positive and significant impact on company profitability. As for partially, first, the issuance of sukuk ijarah has a positive influence on the company's profitability. Second, the Current Ratio has no effect on the company's profitability. Third, the Debt To Equity Ratio has no effect on profitability. Fourth, Size has a significant positive effect on company profitability.